Biomass Extract of Ipomea carnea and Its Inhibition against Trichoderma asperellum - Sutarman (EDP Sciences, 2021)
This study aims to determine the type of metabolites contained in the extraction of Ipomea carnea canopy biomass and its inhibitory effect in vitro against Trichoderma asperellum Tc-Jjr-02 which has been tested as an active ingredient in bio fungicides and biofertilizers. The initial stage of the research is the determination of the metabolites contained in the extract with methanol solvent through Gas Chromatography-Mass Spectrophotometry (GCMS) analysis. The next step was an in vitro test of the extract's inhibitory power to the growth of T. asperellum fungal colonies during the incubation period of up to 96 hours. The results of GCMS analysis of extracts with methanol solvents obtained 24 types of metabolites, some of which can inhibit fungal growth. Crude extract of canopy biomass of I. carnea at a concentration of 2% inhibited the growth of all Trichoderma isolates by 20.97±3.36% (Tc-Jjr-02), 38.15±32.59% (Tc-Sba-01), and 45.30±1.86% (Tc-Jro-01), while at a concentration of 20% inhibited isolates Tc-Sba-01 and Tc-Jro-01 were 35.19±4.90% and 42.59±1.85% in vitro at 96 hours after inoculation, respectively. The isolate of T. esperellum Tc-Jjr-02 has the potential to be formulated with I. carnea biomass as compost in the future.